Stigmatizing Beliefs and Attitudes to Depression in Adolescent School Students in Chile and Colombia - Martínez, Vania; Crockett, Marcelo A.; Jiménez-Molina, Álvaro; Espinosa-Duque, H. Daniel; Barrientos, Elisa; Ordóñez-Carrasco, Jorge L. (Frontiers in Psychology, 2020)
Major depressive disorder (MDD) affects between 4% and 5% of adolescents. However, there is still a huge gap between adolescents who meet criteria for MDD and those who receive mental health care. Stigmatizing attitudes towards depression are among the main barriers to seeking professional help. The aim of this article is to examine the individual characteristics associated with stigmatizing attitudes toward depression in a sample of adolescent school students from Chile and Colombia, and present the adaptation and psychometric properties of the Personal Depression Stigma Scale (DSS-Personal) for both countries. A total of 2971 adolescents, aged 10-19 (M=14.6, SD=1.5), who were recruited from eight schools in Santiago, Chile (n=2022), and eight schools in Medellín, Colombia (n=949), completed the DSS-Personal, the Patient Health Questionnaire (PHQ-9), and a questionnaire of individual sociodemographic characteristics. Factor structure, internal consistency, and validity of the DSS-Personal were assessed. Multiple linear regression models were used to evaluate the association between DSS-Personal scores and sociodemographic information, depression scores, and the use of health services by country. Confirmatory factor analysis supported the unidimensional structure of the DSS-Personal, while the estimated reliability of its scores was acceptable. Results show that DSS-Personal scores were higher in adolescents in Colombia than in Chile (U=9.36, p<0.001). Immigrant status was the only variable significantly related to personal depression stigma in both samples. Being female was associated with lower levels of stigma in adolescents in Chile, while depressive symptoms were associated with lower levels of stigma in adolescents in Colombia. Age, having been diagnosed with depression, and being in pharmacological or psychological treatment were not related to levels of personal depression stigma in either sample. The identified associated factors of personal depression stigma should be considered in the development of anti-stigma campaigns; also, gender differences require special attention. The results of this study suggest that it is important to offer school-based programs to reduce personal stigma, and that specific anti-stigma campaigns should address personal stigma in men and immigrants.